Cultura ambiental y satisfacción con el servicio de limpieza pública en los pobladores del distrito de Belén, provincia de Maynas, región Loreto 2021 - Paredes Vela, Flor de Azucena (2022)
The research aimed to determine the relationship between environmental culture and satisfaction with the public cleaning service in the inhabitants of the district of Belén, province of Maynas; Loreto region 2021, the type of study was descriptive - correlational, in that sense the information collected was analyzed and described, it was also of non-experimental design, therefore, the evaluation was developed without manipulating the real context of the variables. For this, the 71005 inhabitants of the district of Bethlehem were taken as a study population, leaving only 382 people as a sample, to whom a survey was applied, whose information was processed in the statistical programs, which allowed to obtain as results that the environmental culture in the inhabitants is regular, this is evidenced in the environmental values qualified as high, environmental beliefs and attitudes such as regular, however, the level of environmental behavior of people is high. On the other hand, the level of satisfaction with the service is regular, due to the problems present in the operation and management of municipal solid waste, both in storage in public spaces, sweeping of roads and cleaning in public spaces; and solid waste collection. Finally, it has been concluded that there is a significant relationship between environmental culture and satisfaction with the public cleaning service, information that has been corroborated by the correlation coefficient of 0.675, which is positive average, therefore, the determined relationship has a significance (bilateral) at level 0.01, in that sense the null hypothesis is rejected, accepting the research hypothesis.